2009
DOI: 10.3348/kjr.2009.10.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Pure Pulmonary Ground-Glass Opacity Nodules: Prognostic Implications

Abstract: ObjectiveThis study was designed to evaluate follow-up results in terms of patient prognosis for malignant pulmonary nodules depicted as pure ground-glass opacity (GGO) lesion observed at high-resolution CT (HRCT).Materials and MethodsSurgical removal for malignant GGO nodules was accomplished in 58 patients (26 men, 32 women; mean age, 57 years; age range, 29-78 years). Patient prognoses were assessed by patient clinical status and the presence of changes in nodule size determined after a follow-up HRCT exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 18 publications
0
25
1
Order By: Relevance
“…12,[23][24][25][26][27][28][29] This observation is made in both Asian and North American populations. The proportion of nonsmokers (30-80%) varies with the regional prevalence of smoking but is always greater than that of the general prevalence in patients with lung cancer in that region.…”
Section: Descriptive Characteristicsmentioning
confidence: 67%
“…12,[23][24][25][26][27][28][29] This observation is made in both Asian and North American populations. The proportion of nonsmokers (30-80%) varies with the regional prevalence of smoking but is always greater than that of the general prevalence in patients with lung cancer in that region.…”
Section: Descriptive Characteristicsmentioning
confidence: 67%
“…Park et al 22 reported an excellent prognosis in a cohort of 58 patients with malignant pure GGOs who underwent surgical resection. There was no incidence of local recurrence or metastasis occurring in any of these patients after 24 months of follow up.…”
Section: Discussionmentioning
confidence: 98%
“…19 However, malignant GGO lesions can remain stable in size for as long as 36 months. 20 In addition, during the observation period, some malignant tumours will progress from being resectable to unresectable. 21 GGO lesions have been reported to have a good prognosis, and, in most cases, their pathological features are minimally invasive.…”
Section: Discussionmentioning
confidence: 99%